Cloning and characterization of TaSnRK2.3, a novel SnRK2 gene in common wheat - Tian, Shanjun (Oxford University Press, 2013)
Environmental stresses such as drought, salinity, and cold are major adverse factors that significantly affect agricultural productivity. Protein phosphorylation/dephosphorylation is a major signalling event induced by osmotic stress in higher plants. Sucrose non-fermenting 1-related protein kinase 2 (SnRK2) family members play essential roles in the response to hyperosmotic stresses in plants. In this study, the TaSnRK2.3 gene, a novel SnRK2 member was cloned, and three copies located on chromosomes 1A, 1B, and 1D were identified in common wheat. TaSnRK2.3 was strongly expressed in leaves, and responded to polyethylene glycol, NaCl, abscisic acid, and cold stresses. To characterize its function, transgenic Arabidopsis overexpressing TaSnRK2.3–GFP controlled by the cauliflower mosaic virus 35S promoter was generated and subjected to severe abiotic stresses. Overexpression of TaSnRK2.3 resulted in an improved root system and significantly enhanced tolerance to drought, salt, and freezing stresses, simultaneously demonstrated by enhanced expression of abiotic stress-responsive genes and ameliorative physiological indices, including a decreased rate of water loss, enhanced cell membrane stability, improved photosynthetic potential, and significantly increased osmotic potential and free proline content under normal and/or stressed conditions. These results demonstrate that TaSnRK2.3 is a multifunctional regulator, with potential for utilization in transgenic breeding for improved abiotic stress tolerance in crop plants.